Seismic Constraints on the Spin Evolution of Slowly Rotating Young Intermediate-mass Stars - Kunal H. Singh; Subrata Kumar Panda; Shravan M. Hanasoge; Siddharth Dhanpal (The Astrophysical Journal, 2025)
δ Scuti stars are hot, rapid rotators and a poorly understood class of pulsators. Asteroseismology provides the only means with which to probe their interior dynamics. However, their complex and unexplained oscillation patterns restrict analyses to only a small fraction with interpretable pulsations. Here, we identify 5381 δ Scuti stars from 63 sectors of TESS observations, of which 300 had interpretable oscillations, with 24 showing rotational splittings. We inferred compositions and ages ( τ ) for the 300 stars, finding them in near-zero-age-main-sequence (ZAMS) states, and measured the mean envelope rotation rates (〈 f _rot 〉) for 24 of them. Analyzing their age-dependent rotation, we found that these stars essentially exhibit weak to no spin-down while evolving past the ZAMS across a narrow time span during which they show regular pulsations. A quantitative fit to their spin evolution results in a trend f _rot ( d ^−1 ) ∝ ( τ /Gyr) ^−0.048 ± 0.016 , much slower than the spin-down of cooler late-type stars due to magnetic braking (Skumanich’s law: f _rot ( d ^−1 ) ∝ ( τ /Gyr) ^−0.5 ). Based on stellar evolution calculations, we show that this weak spin-down is consistent with the gradual increase in the moment of inertia.